1995
DOI: 10.1007/bf02638899
|View full text |Cite
|
Sign up to set email alerts
|

Fatty acid vinyl esters as acylating agents: A new method for the enzymatic synthesis of monoacylglycerols

Abstract: Lipase-catalyzed synthesis of monoacylglycerols (MAG) was performed by transesterification reactions between fatty acid vinyl esters and either glycerol (1) or 1,2-O-isopropylidene-rac-glycerol (2), without solvents or in the presence of npentane. Vinyl decanoate, vinyl laurate, vinyl stearate and vinyl palmitate have been converted to the corresponding monoacylglycerols. As expected for the reaction with 1, a mixture of mono-, di-and triacylglycerols was synthesized. The highest concentrations of MAG were ach… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
21
0
1

Year Published

1998
1998
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(22 citation statements)
references
References 20 publications
0
21
0
1
Order By: Relevance
“…Enol esters have also been used as acyl donors which shift the position of the equilibrium because they cause irreversible tautomerization of the vinyl alcohol or isopropenyl alcohol by-product. In a short reaction time, 100% conversion of long-chain fatty-acid vinyl esters was achieved (12,13).…”
mentioning
confidence: 99%
“…Enol esters have also been used as acyl donors which shift the position of the equilibrium because they cause irreversible tautomerization of the vinyl alcohol or isopropenyl alcohol by-product. In a short reaction time, 100% conversion of long-chain fatty-acid vinyl esters was achieved (12,13).…”
mentioning
confidence: 99%
“…Acylation of the isopropylidene derivative of glycerol has been widely used for the synthesis of monoacylglycerols (8)(9)(10). Our initial studies with isopropylidene glycerol were carried out in hexane solvent at 60°C using Lipozyme TM as the catalyst and dimethyl sebacate as the acyl donor.…”
Section: Resultsmentioning
confidence: 99%
“…The latter strategy, however, deals with substrates that often have very different solubility characteristics, which often inhibits their reaction with each other. A number of publications have addressed this problem by devising different methods to modify the solubility of glycerol, for example by adsorption onto inert supports (5-7), use of the isopropylidene protecting group (8)(9)(10), or complexation with phenyl boronic acid (PBA) (11,12). Other approaches to overcoming the glycerol solubility limitation include carrying out the reaction with substrates in biphasic systems (13), by microemulsion (14), or by addition of water to the reaction media (15).…”
mentioning
confidence: 99%
“…The reaction can be performed at lower temperatures to minimize acyl migration [43]. Bornscheuer and Yamane [45] used this technique for regiospecific synthesis of sn-1(3)-monoacylglycerol (MAG). They found that transesterification of FA vinyl ester and isopropylidene glycerol in pentane produced MAG in higher yield and in shorter time compared to direct esterification with free acids or transesterification with FA esters.…”
Section: Symmetrical Tag (Xyx)mentioning
confidence: 99%